2002
DOI: 10.1002/app.10943
|View full text |Cite
|
Sign up to set email alerts
|

Use of novel hydrogels based on modified cellulosics and methacrylamide for separation of metal ions from water systems

Abstract: ABSTRACT:Interpenetrating networks (IPNs) based on extracted cellulose and its derivatives such as hydroxypropyl cellulose (HPC), cyanoethylcellulose, hydroxyethylcellulose, hydrazinodeoxycellulose, cellulosephosphate with methacrylamide (MAAm), and N,N-methylene bisacrylamide were synthesized at reaction conditions evaluated for optimum network yield as a function of irradiation dose, concentrations of monomer and crosslinker, and amount of water. These networks were used in sorption of Fe 2ϩ , Cu 2ϩ , and Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 12 publications
1
54
0
Order By: Relevance
“…Partial hydrolysis should enhance metal ion uptake, as it increases polymer-metal ion and polymer-water interactions. 19 From Table IIIb it is understandable that most of the hydrolyzed samples do not absorb any Cr 61 ions while it is lower than the unhydrolyzed in case of Cu 21 . In hydrogels loaded with Cr 61 breakdown of the networks was observed due to oxidation of the pectin chains.…”
Section: Sorption Of Metal Ions On Hydrogelsmentioning
confidence: 94%
See 2 more Smart Citations
“…Partial hydrolysis should enhance metal ion uptake, as it increases polymer-metal ion and polymer-water interactions. 19 From Table IIIb it is understandable that most of the hydrolyzed samples do not absorb any Cr 61 ions while it is lower than the unhydrolyzed in case of Cu 21 . In hydrogels loaded with Cr 61 breakdown of the networks was observed due to oxidation of the pectin chains.…”
Section: Sorption Of Metal Ions On Hydrogelsmentioning
confidence: 94%
“…Sorption studies were carried as reported earlier. 19 Hydrogels were immersed for 24 h in 20.00 mL solutions of known strength. Filtrates of the solutions were analyzed for concentration of rejected ions on DR 2010 Spectrophotometer (M/s.…”
Section: Metal Ion Sorption Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dragan [69] described the studies of interpenetrating polymer networks (IPN) hydrogels based on biopolymeric materials, such as, chitosan, alginate, starch, and other polysaccharides. Chauhan and Mahajan [70] apud Dragan [69] described the use of IPN based on a combination of biopolymers with poly(methacrylamide) for metal ion sorption in aqueous solution. They noticed that the sorption capacity of the material drastically increased after inserting cellulose derivatives in the polymer network.…”
Section: Superabsorbent Polymer Hydrogels As Soil Conditionersmentioning
confidence: 99%
“…Conventional treatment techniques for removing dissolved heavy-metal ions from wastewater by chemical treatment, ultrafiltration or their combination do not always sufficiently remove contaminants to meet pollution control limits [1][2][3][4]. Recently, many types of hydrogel such as poly(acrylic acid), poly(acrylic acid) grafted cellulose and macroporous poly(glycidyl methacrylate-co-ethylene glycol dimethacrylate) have been reported for the removal of Cu(II), Cd(II) and Cr(III) under competitive conditions [5][6][7].…”
Section: Introductionmentioning
confidence: 99%